2019
DOI: 10.1002/pen.25245
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Grain Husks Derived Lignocellulose Filler Containing Polypropylene Composites

Abstract: Oat and spelt husks (OH and SH, respectively) lignocellulosic biomass derived fillers have been compared with commercial wood flour (WF) in respects to their morphology, chemical composition, bulk density, aspect ratio, and thermal stability. OH and SH have been obtained by both mechanical milling and steam explosion auto‐hydrolysis treatment at various processing conditions. Reinforcement efficiency of OH and SH derived lignocellulosic biomass fillers on the flexural properties of maleic acid‐grafted polyprop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
0
9
0
2
Order By: Relevance
“…The problem caused by the improper disposal of the synthetic polymer can be minimized by inclusion of more and more bio-based materials in the composites. [1][2][3][4][5] The involvement of materials derived from renewable sources in the composite not only increases the biodegradability of the composite but also decreases the cost of production. [6,7] Thermoplastic starch (TPS) is one of such material which has huge potential as biopolymer.…”
Section: Introductionmentioning
confidence: 99%
“…The problem caused by the improper disposal of the synthetic polymer can be minimized by inclusion of more and more bio-based materials in the composites. [1][2][3][4][5] The involvement of materials derived from renewable sources in the composite not only increases the biodegradability of the composite but also decreases the cost of production. [6,7] Thermoplastic starch (TPS) is one of such material which has huge potential as biopolymer.…”
Section: Introductionmentioning
confidence: 99%
“…[4] However, the PP polymer is non-polar, which will cause poor interfacial bonding strength when applying it to the polar wood-based substrates. [5][6][7] Numerous studies have focused on improving the interfacial adhesion between PP polymer and wood substrates, which can be achieved by modifying the adhesives used by the addition of appropriate ternary compatibilizers. [8][9][10] In addition, the activation of the PP polymer can be improved by plasma treatment, [11] chlorination, [12] and isocyanate silane grafting, [13] while deligninfication, [14] heat treatment, [15] and enzyme treatment [16] of the wood substrates have been aimed at the reduction of the polarity of the wood.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in our previous research, it was demonstrated that the addition of either mechanically milled or steam-explosion-treated oat or spelt husk flat microfibres allows more than a twofold increase in the modulus of elasticity, as well as an improvement in tensile and flexural strength of PP composites in comparison with the neat polymer matrix. In contrast, the ultimate elongation of the grain husk microfiller-containing systems was larger than that of the wood flour filler-modified counterpart [ 16 ].…”
Section: Introductionmentioning
confidence: 99%